Next Generation Repositories: Invenio - Yamaji, Kazutsuna (2018)
An Overview of Invenio: •Flexible –Inveniois a framework for building large scale digital repositories: RDM, Media Archive, Institutional Repository, Search Engine, ILS, Brokers.•Scalable –Handles 100M records and petabytes of files and integrates with any storage system.•Powerful search –with the full capabilities of Elasticsearch such as geospatial queries.•Born for the web –REST APIs everywhere.•Data model agnostic –Natively based on JSON from storage to indexing.•Best of Open Source-Built on top of the best: Elasticsearch, PostgreSQL/MySQL, Flask & Python